Targeted Disruption of V600E-Mutant BRAF Gene by CRISPR-Cpf1 - Meijia Yang (Molecular Therapy: Nucleic Acids, 2017)
BRAF-V600E (1799T > A) is one of the most frequently reported driver mutations in multiple types of cancers, and patients with such mutations could benefit from selectively inactivating the mutant allele. Near this mutation site, there are two TTTN and one NGG protospacer-adjacent motifs (PAMs) for Cpf1 and Cas9 CRISPR nucleases, respectively. The 1799T > A substitution also leads to the occurrence of a novel NGNG PAM for the EQR variant of Cas9. We examined the editing efficacy and selectivity of Cpf1, Cas9, and EQR variant to this mutation site. Only Cpf1 demonstrated robust activity to induce specific disruption of only mutant BRAF, not wild-type sequence. Cas9 recognized and cut both normal and mutant alleles, and no obvious gene editing events were observed using EQR variant. Our results support the potential applicability of Cpf1 in precision medicine through highly specific inactivation of many other gain-of-function mutations. Keywords: Cpf1, targeted therapy, BRAF V600E